2019
DOI: 10.1002/ep.13229
|View full text |Cite
|
Sign up to set email alerts
|

Mulching with crop straws influences cadmium accumulation of Cyphomandra betacea seedlings

Abstract: Mulching with plant straws on cadmium (Cd) contaminated soil can reduce Cd accumulation in crop plants. In this pot experiment, Cd‐contaminated soil was mulched with the straw of rice, wheat, rape, or broad bean, and their effects on the growth and Cd accumulation of Cyphomandra betacea seedlings were studied. Mulching with the straw of rice or broad bean increased the root, stem, leaf, and shoot biomasses of C. betacea seedlings, and increased the chlorophyll contents in leaves of C. betacea seedlings, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…betacea seedlings, but mulching with G. parviflora, wheat and rape straw significantly decreased the biomass. 16,36 This showed that different accumulator plant straw can have different effect on growth of the same plant. In this study, applying B. biternata straw increased the biomass of Z. acidojujuba seedlings, while applying B. pilosa straw decreased the biomass, applying B. parviflora straw just increased the root biomass.…”
Section: Discussionmentioning
confidence: 99%
“…betacea seedlings, but mulching with G. parviflora, wheat and rape straw significantly decreased the biomass. 16,36 This showed that different accumulator plant straw can have different effect on growth of the same plant. In this study, applying B. biternata straw increased the biomass of Z. acidojujuba seedlings, while applying B. pilosa straw decreased the biomass, applying B. parviflora straw just increased the root biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Under heavy metal contaminated soil, it is important to adjust plant heavy metal absorption by changing the external environment, which is important for alleviating the heavy metal stress on the plants [37]. Certain studies showed that adding straws from different crops to soil reduced the heavy metal uptake of plants [37,38].…”
Section: Content In N Officinalementioning
confidence: 99%
“…Under heavy metal contaminated soil, it is important to adjust plant heavy metal absorption by changing the external environment, which is important for alleviating the heavy metal stress on the plants [37]. Certain studies showed that adding straws from different crops to soil reduced the heavy metal uptake of plants [37,38]. For hyperaccumulators or accumulators, certain plant straws (such as Youngia erythrocarpa and Cardamine hirsuta) promoted the Cd uptake of the Cd-hyperaccumulator Galinsoga parviflora and the Cd-accumulator Capsella bursa-pastoris, while other plant straws inhibited these properties [8,35,36,[39][40][41].…”
Section: Content In N Officinalementioning
confidence: 99%